2005
DOI: 10.1038/sj.bjp.0706089
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the functional roles of α1‐adrenoceptor subtypes in mouse carotid arteries using knockout mice

Abstract: 1 a 1 -Adrenoceptor (AR) subtypes in mouse carotid arteries were characterised using a combination of agonist/antagonist pharmacology and knockout (KO) mice. 2 Phenylephrine (PE) was most potent in the a 1B -KO (pEC 50 ¼ 6.970.2) followed by control (pEC 50 ¼ 6.370.06) and a 1D -KO (pEC 50 ¼ 5.570.07). Both N-[5-(4,5-dihydro-1H-imidazol-2yl)-2-hydroxy-5,6,7,8-tetrahydronaphthalen-1-yl] methanesulphonamide hydrobromide (A-61603) and 5-hydroxytryptamine (5-HT) were more potent in the a 1D -KO (pEC 50 ¼ 7.470.27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
(45 reference statements)
3
20
0
Order By: Relevance
“…Such a finding provides a good explanation for the long-standing mystery in the ␣ 1 adrenoceptor field: that ␣ 1D receptors could not be detected in native tissue using high-affinity binding of BMY 7378 (Yang et al, 1997(Yang et al, , 1998, despite a high level of mRNA expression. This proposal is also consistent with a number of data reported with KO animals, such as increased affinity of the ␣ 1D selective antagonist BMY 7378 in ␣ 1B knockout mice (Deighan et al, 2005) or the potent BMY 7378 antagonist activity in left ventricular phenylephrineinduced pressure observed in ␣ 1A -␣ 1B double KO mice. Taken together, these different findings are consistent with the existence of ␣ 1B -␣ 1D heterodimers in native tissue.…”
Section: G the ␣ 1b And ␣ 1d Adrenoceptorssupporting
confidence: 80%
“…Such a finding provides a good explanation for the long-standing mystery in the ␣ 1 adrenoceptor field: that ␣ 1D receptors could not be detected in native tissue using high-affinity binding of BMY 7378 (Yang et al, 1997(Yang et al, , 1998, despite a high level of mRNA expression. This proposal is also consistent with a number of data reported with KO animals, such as increased affinity of the ␣ 1D selective antagonist BMY 7378 in ␣ 1B knockout mice (Deighan et al, 2005) or the potent BMY 7378 antagonist activity in left ventricular phenylephrineinduced pressure observed in ␣ 1A -␣ 1B double KO mice. Taken together, these different findings are consistent with the existence of ␣ 1B -␣ 1D heterodimers in native tissue.…”
Section: G the ␣ 1b And ␣ 1d Adrenoceptorssupporting
confidence: 80%
“…For example, knockout studies in which the gene for one or more ␣ 1 -AR subtypes has been inactivated have hinted at potential crosstalk between the various subtypes. Thus, in keeping with the present findings, it has been demonstrated that removal of the ␣ 1B -AR leads to the appearance of binding sites with high affinity for BMY-7378 (Daly et al, 2002;Deighan et al, 2005;Hosoda et al, 2005). This suggests that the ␣ 1D -AR is indeed expressed in the vasculature and contributes to maintenance of blood pressure-a contention that is also evident from the reduced blood pressure and impaired vasoconstrictor responses to norepeinephrine of ␣ 1D -knockout mice (Tanoue et al, 2002)-but that its expression is masked by the coincident expression of the ␣ 1B -AR.…”
supporting
confidence: 70%
“…In addition, a recent study using ␣ 1 -AR knockout mice found that ␣ 1D -AR and ␣ 1D -/␣ 1B -AR knockout mice had a significant decrease in mean arterial blood pressure, whereas ␣ 1B -AR knockout mice did not, suggesting that ␣ 1D -/␣ 1B -ARs may act cooperatively to regulate blood pressure (Hosoda et al, 2005). Additional evidence for a physiological role of ␣ 1B -AR/␣ 1D -AR heterodimers was provided from functional studies of isolated mouse carotid arteries, in which the potency of phenylephrine was significantly decreased in ␣ 1D -AR knockout mice yet unchanged in ␣ 1B -AR knockout mice Downloaded from (Deighan et al, 2005). These findings raise the possibility that specific heterodimers respond supermaximally to agonist stimulation.…”
Section: Discussionmentioning
confidence: 90%
“…However, BMY 7378 detected only a single population of low-affinity binding sites in radioligand binding experiments (Bockman et al, 2004), which is consistent with our findings suggesting that coexpression of ␣ 1B -and ␣ 1D -ARs results in the masking of high-affinity ␣ 1D -AR binding sites. In addition, the affinity of BMY 7378 in inhibiting phenylephrine-mediated contraction was found to be significantly increased in isolated carotid arteries from ␣ 1B -AR knockout mice (Deighan et al, 2005), and phenylephrinestimulated increases in left ventricular-developed pressure were only inhibited by BMY 7378 in ␣ 1A -/␣ 1B -AR double knockout mice (Turnbull et al, 2003). These unusual findings could be explained by a model wherein the knockout of ␣ 1B -ARs from native tissues results in the unmasking of ␣ 1D -AR binding sites with high affinity for BMY 7378, which would be predicted from the results of our cellular studies reported here.…”
Section: Discussionmentioning
confidence: 99%